2017
DOI: 10.1002/cb.1670
|View full text |Cite
|
Sign up to set email alerts
|

Switching behaviour as a function of number of options: How much is too much for consumer choice decisions?

Abstract: The number of alternatives for consumers in almost all purchase situations is increasing at an extremely rapid pace. Although more choices may have many benefits to the consumers, recent studies on choice overload have found that choosing from large alternatives may lead to negative consequences. Majority of the choice overload research has compared only two groups of small versus large assortment size. In extant literature, there is no clarity as to what are small and large assortment sizes. Assortment size u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In contrast, buyers of high‐involvement products need to follow a thorough decision‐making process where the possibility of financial and non‐financial risks is higher than the low involvement products (Arora & Mail, 2018). Further, the high involvement products generally have high personal importance and sometimes situational importance (Sharma & Nair, 2017).…”
Section: Literaturementioning
confidence: 99%
“…In contrast, buyers of high‐involvement products need to follow a thorough decision‐making process where the possibility of financial and non‐financial risks is higher than the low involvement products (Arora & Mail, 2018). Further, the high involvement products generally have high personal importance and sometimes situational importance (Sharma & Nair, 2017).…”
Section: Literaturementioning
confidence: 99%
“…Their choice decision has attracted great attention from both researchers and practitioners (Wang, Sun, Niraj, Chung, & Su, 2019). Wang et.al (2019) suggested that it is affected significantly by a set of choice composition, although Sharma and Nair (2017) believed that customers may begin to experience choice overload as a result of extremely various assortments.…”
Section: Consumers' Choice Decisionmentioning
confidence: 99%
“…The influence of assortment size on consumer perception and consequent behavior has already been explored in the literature. Previous research demonstrates, for example, that assortment size determines the probability of consumers switching their earlier choices (Sharma & Nair, 2017) and deferring purchase (Iyengar, Huberman, & Jiang, 2004). Additionally, large assortments interfere negatively in preference construction (Chernev, 2003;Iyengar & Lepper, 2000), and lead to increasingly negative emotions, such as disappointment and regret (Schwartz, 2000).…”
Section: Hypothesesmentioning
confidence: 99%
“…Because of the relevance of repetition for this phenomenon, H1 proposes that when repetition is cued, consumers predict future hedonic adaptation. Wilson and Gilbert (2008) Galak et al 2009Sevilla et al 2016Assortment variety Sharma and Nair (2017) These studies investigate how assortment variety influences choice, enjoyment or adaptation (which includes satiation and habituation). Given the pervasive effects of variety on adaptation, these studies inform the proposition of H2 and the variety manipulations in study 2.…”
Section: Manipulated Variablesmentioning
confidence: 99%